Integrated design and operation of a transparent optical network a systematic approach to include physical layer awareness and cost function. - Politi, Christina T.
The manner and exact timing of the evolution of the widely used DWDM infrastructure to a transparent optical network is judged on economic circumstances and network performance. In this context this article elaborates on a methodology developed within the Project 1ST NOBEL, for integrating cost functions and other design constraints into the planning of a DWDM network while considering this evolution perspective to a transparent optical network. This systematic approach builds upon the experience of static network design and is substantiated by specific examples in this article.
Keywords: DWDM insfrastructure; Project 1st NOBEL; Cost function; Design constraints; Economic circumstances; Network performance; Physical layer awareness; Static network design; Transparent optical network